A Global Integration Strategy for the Mediterranean Countries : Open Trade and Market Reforms - Havrylyshyn, Oleh (International Monetary Fund, 1997)
The economy of the Mediterranean region countries - which in the present study include Algeria, Egypt, Jordan, Lebanon, Morocco, Syria, Tunisia, as well as Israel and Turkey - experienced a period of strong and dynamic economic development in the late 1970s and early 1980s. But since the 1980s these economies have experienced a much less dynamic evolution and tended toward stagnation. This paper by Oleh Havrylyshyn, presents an assessment of the experience of these economies in a framework of a broad trade strategy perspective for Mediterranean countries, and examines prospects for the future.